European household spending and socio-economic impacts on food behavior during the first wave of COVID-19 - Hristov, Hristo; Millard, Jeremy; Pravst, Igor; Janssen, Meike (Frontiers in Nutrition, 2022)
This paper provides a European-level analysis using a large scale survey of 13 countries to examine the power of relevant economic and socio–demographic characteristics to account for changes in food consumption and purchasing behaviour during Covid-19. It does this by focusing on a two level analysis of subject-related predictors highlighted in many existing country-level studies in order to test the generality of their significance. The Level 1 predictors relate to the the individual households participating in the survey consisting of household composition, education and location, as well as three types of perceived Covid-19 risks of infection, severity and anxiety. Level 2 relates to the national level, and especially to the financial situation measured by the mean national Actual Individual Consumption (AIC) per capita in PPP, of the countries in which the households reside. In terms of changes in food consumption, results show that household composition, education and the perceived risk of Covid 19 infection and severity are significant predictors, although there are some differences between the two levels. Possible explanations are that actually putting food into one’s body in the context of the pandemic is related to a household’s financial situation, its composition especially the presence or absence of children and older people, and its educational attainment, and through these to the perception of Covid-19 infection and severity risks. Changes in food purchasing react significantly to the same predictors, but additionally to all other predictors at both household and AIC levels. The household’s location and perceived Covid-19 anxiety risks are thus also significant. Food purchasing depends much more on factors operating at both the individual household level and the AIC level together, for example households’ access to food is affected by both national and local lockdown restrictions that vary according to the location of the household.